Pemanfaatan Lingkungan Alam Sekitar Sebagai Sumber Belajar Dalam Pembelajaran IPAS - Hilda Anggun Utami; hilda hilda anggun (JOIN: Journal of Indonesian Education and Learning, 2026)
Natural and Social Sciences learning is designed to build students' understanding of various natural and social phenomena in an integrated manner. However, the implementation of IPAS learning in schools is still dominated by the use of textbooks and classroom learning activities, so that the learning experiences gained by students are not very contextual. This study aims to examine the use of the natural environment as a learning resource in IPAS learning, including the forms of application, benefits obtained, and obstacles encountered in its implementation. This study uses a qualitative approach with a literature study method through the analysis of various relevant books and scientific journal articles. The results of the study show that the surrounding natural environment has great potential as a real, contextual, and meaningful learning resource. The use of the natural environment in science education can increase students' motivation to learn, understanding of concepts, critical thinking skills, and concern for the environment. However, the implementation of environmentbased learning still faces various obstacles, such as time constraints, teacher readiness, and school policy support. Therefore, systematic planning and institutional support are needed so that the use of the natural environment as a learning resource can run optimally.